2014
DOI: 10.1111/dote.12216
|View full text |Cite
|
Sign up to set email alerts
|

Brief report: the length of newly diagnosed Barrett's esophagus may be decreasing

Abstract: Few studies have examined the temporal trends of length in newly diagnosed Barrett's esophagus (BE) and arrived at conflicting results. The aim of this study was to identify whether there has been a change over time in the length of BE at the time of diagnosis. This is a retrospective, single-center, observational study from Houston, Texas on newly diagnosed BE between 2008 and 2013. All cases were defined by the presence of endoscopically visible BE and histologic confirmation of intestinalized columnar epith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…There are also limited data suggesting that BO length actually remains constant over time regardless of medical or surgical treatment 8 20–22. Resolving this uncertainty is key to addressing the increased risk of malignancy with BO length and may have an impact on surveillance recommendations and endoscopic therapy 6 7 9…”
Section: Introductionmentioning
confidence: 99%
“…There are also limited data suggesting that BO length actually remains constant over time regardless of medical or surgical treatment 8 20–22. Resolving this uncertainty is key to addressing the increased risk of malignancy with BO length and may have an impact on surveillance recommendations and endoscopic therapy 6 7 9…”
Section: Introductionmentioning
confidence: 99%
“…They also reported a decrease in the proportion of patients being diagnosed with BE >3 cm. 32 Kendall and Whiteman 28 found that the median length of long-segment BE decreased from 10 cm to 5 cm from 1990 to 1998 and 2002, and this was accompanied by an increase in the diagnosis of short-segment BE in that same time period.…”
Section: Discussionmentioning
confidence: 98%